2015
DOI: 10.3389/fevo.2015.00134
|View full text |Cite
|
Sign up to set email alerts
|

Early Environmental Conditions Shape Personality Types in a Jumping Spider

Abstract: Individuals of many species across the animal kingdom are found to be less plastic than expected, even in behavioral traits. The existence of consistent behavioral differences between individuals, termed "personality differences", is puzzling, since plastic behavior is considered ideal to enable animals to adaptively respond to changes in environmental conditions. In order to elucidate which mechanisms are important for the evolution of personality differences, it is crucial to understand which aspects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 86 publications
(112 reference statements)
2
38
0
Order By: Relevance
“…For M. muscosa , Liedtke et al . () showed that the exploration tendency was higher in spiders from the physically enriched treatment (P), which correlates with our findings of a larger AB in spiders from this treatment group. In addition, spiders in treatment D were much more restricted in space than individuals from treatment P, which may have resulted in reduced locomotory activity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For M. muscosa , Liedtke et al . () showed that the exploration tendency was higher in spiders from the physically enriched treatment (P), which correlates with our findings of a larger AB in spiders from this treatment group. In addition, spiders in treatment D were much more restricted in space than individuals from treatment P, which may have resulted in reduced locomotory activity.…”
Section: Discussionsupporting
confidence: 91%
“…weekly. For a more detailed rearing protocol, see Liedtke et al (2015). Wildcaught adult spiders (W) were used for comparison.…”
Section: Specimen Collection and Rearing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many behavioral traits have been shown to be plastic in response to experiences during development (Sinn et al 2008; Butler et al 2012; DiRienzo et al 2012; Niemelä et al 2012a; DiRienzo et al 2015; Liedtke et al 2015; DiRienzo and Montiglio 2016). Developmental plasticity is largely assumed to be an adaptive, and mostly irreversible, response where an organism experiences an environmental cue during a sensitive period and adjusts its traits accordingly for the future (West-Eberhard 2003; Groothuis and Trillmich 2011).…”
Section: Discussionmentioning
confidence: 99%
“…During ontogeny, personality traits also change within individuals. These changes in temporal consistency may arise due to differential exposure to environmental conditions or to individual differences in developmental plasticity when individuals are exposed to the same conditions (Stamps & Krishnan, 2014;Liedtke et al, 2015). Personality variation may be maintained because there are multiple optima in different conditions, over time or space (Boon, Réale & Boutin, 2007), such as variations in predation pressure (Réale & Festa-Bianchet, 2003), food availability (Dingemanse et al, 2004), or social condition (Both et al, 2005).…”
Section: Introductionmentioning
confidence: 99%